Effects of animacy on the processing of morphological Number: a cognitive inheritance?. (March 2020) - Zanini, Chiara; Rugani, Rosa; Giomo, Dunia; Peressotti, Francesca; Franzon, Francesca
Abstract : Language encodes into morphology part of the information present in the referential world. Some features are marked in the great majority of languages, such as the numerosity of the referents that is encoded in morphological Number. Other features do not surface as frequently in morphological markings, yet they are pervasive in natural languages. This is the case of animacy, that can ground Gender systems as well as constrain the surfacing of Number. The diffusion of numerosity and animacy could mirror their biological salience at the extra-linguistic cognitive level. Human extra-linguistic numerical abilities are phylogenetically ancient and are observed in non-human animal species, especially when counting salient animate entities such as social companions. Does the saliency of animacy influence the morphological encoding of Number in language processing? We designed an experiment to test the encoding of morphological Number in language processing in relation to animacy. In Italian, Gender and Number are mandatorily expressed in a fusional morpheme. In some nouns denoting animate referents, Gender encodes the sex of referents and is semantically interpretable. In some other animate nouns and in inanimate nouns, Gender is uninterpretable at the semantic level. We found that it is easier to inflect for Number nouns when the inflectional morpheme is interpretable with respect to a semantic feature related to animacy. We discuss the possibility that the primacy of animacy in counting is mirrored in morphological processing and that morphology is designed to easily express information that is salient from a cognitive point of view.